Crystal structure of bis[μ2-(N,N-diethylcarbamodithioato-κS:κS,κS′)]-bis(triethylphosphine-P)-di-silver(I), C22H50Ag2N2P2S4 - Yeo, Chien Ing *; Tan, Yi Jiun *; Shiomitsu, Aya *; Chew, Jactty *; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C22H50Ag2N2P2S4, triclinic, P1̄ (no. 2), a = 9.0672(2) Å, b = 11.2091(3) Å, c = 16.6853(4) Å, α = 91.097(2)°, β = 90.363(2)°, γ = 110.989(2)°, V = 1582.85(7) Å3, Z = 2, R gt(F) = 0.0241, wR ref(F 2) = 0.0653, T = 100(2) K.